Warfarin: do we need genotype-based dose prediction? - Yenny, Yenny (Universa Medicina, 2010)
For the treatment and prevention of thrombo-embolic disease, the most frequently used anticoagulant drug worldwide is warfarin, an oral coumarin derivative, with more than 30 million prescriptions written for this drug in the United States in 2004.(1) The drug has a narrow therapeutic index and its metabolism varies by as much as a factor of 10 among individual patients, making warfarin therapy difficult to manage. Hemorrhagic complication rates of warfarin are estimated to be 5-7.9% for major (life threatening) hemorrhage and 14-36% for minor hemorrhage (e.g. nosebleeds, microscopic hematuria).(2) This condition makes it difficult to establish the appropriate dose of warfarin.